Conformational isomerism in cyclic peptoids and its specification. Issue 46 (22nd November 2017) - D'Amato, A.; Schettini, R.; Della Sala, G.; Costabile, C.; Tedesco, C.; Izzo, I.; De Riccardis, F.
Abstract : Conformational chirality is an emerging and neglected property of rigid cyclic peptoids determining structural, catalytic, and biological properties. The present contribution analyzes its impact and sets the configurational rules to define it. Abstract : Most of the structural studies made on the secondary structure of peptoids describe their geometric attributes in terms of the classic Ramachandran plot (based on the local analysis of ω, ψ, χ, φ dihedral angles). However, little intuitive understanding is available from internal coordinates when stereochemistry is involved. In this contribution we list all the conformationally stable cyclic peptoids reported up to the year 2017 and propose a simple method to define their geometric arrangement in terms of planar chirality. Evidence of conformational isomerism (due to the long average time of single bond rotation) and conformational chirality (induced by the absence of roto-reflection axes) in this promising class of synthetic macrocycles is provided by NMR spectroscopy (using Pirkle's alcohol as chiral solvating agent) and careful evaluation of X-ray crystallographic studies. The full understanding of the oligomeric macrocycles' structural properties and the clear framing of their conformational isomerism in a proper conceptual scheme is fundamental for future application of peptoids in asymmetric synthesis, chiral recognition and supramolecular chemistry.